Semi-solid lithium ion secondary battery

By using a solid electrolyte membrane with specific particle size and composition in lithium-ion secondary batteries, electronic insulating materials are filled to prevent dendrites from growing, the internal short circuit and high resistance problems caused by dendrites in lithium-ion secondary batteries are solved. Excellent charge and discharge cycle characteristics and ion conductivity are achieved.

CN119208709APending Publication Date: 2024-12-27FUJIFILM CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411313202.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-10-30
Filing Date
2020-10-28
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The growth of dendrites in lithium-ion secondary batteries leads to internal short circuit problems. Although the prior art can suppress dendrites' growth, it is easy to lead to high resistance, affecting the charge and discharge cycle characteristics and ion conductivity of the battery.

Method used

A solid electrolyte film with 10 to 500 nm electron insulating inorganic particles is used, and a hot melt solidified substance of an inorganic solid electrolyte particle larger than an insulating inorganic particles and a hot melt of an electronic insulating material that is solid at 100°C and is hot melted below 200°C. Fill the voids of the solid electrolyte layer and ensure that the electronic insulating material is in a non-crystalline state through a specific layer structure and material combination, forming a film with a thickness of 0.7 to 1.3 times that of the inorganic solid electrolyte particles.

Benefits of technology

It realizes excellent charging and discharge cycle characteristics and ion conductivity of lithium-ion secondary batteries, effectively prevents dendrites from growing, reduces battery resistance, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208709A_ABST
    Figure CN119208709A_ABST
Patent Text Reader

Abstract

The invention relates to a semi-solid-state lithium ion secondary battery, which comprises a solid electrolyte membrane (22), a lithium ion battery (30) and a lithium ion battery (40), an inorganic solid electrolyte particle (25) which is larger than the electron-insulating inorganic particle (26) and has electrolyte resistance and ion conductivity; and a heat-melt coagulum (27) of an electron-insulating material, which fills the gaps between the solid particles and is heat-melted in a specific temperature range, and which has an electron-insulating inorganic particle (26) having a particle diameter of 10-500 nm. A positive electrode layer; and a negative electrode layer in which a hot-melt coagulated material (27) of an electronic insulating material is in an amorphous state, the inorganic solid electrolyte particles (25) in the solid electrolyte membrane (22) are actually arranged in a single layer, and at least one of the positive electrode layer and the negative electrode layer includes a semi-solid active material layer containing an electrolyte solution.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application. The international application number of the original application is PCT / JP2020 / 040486, the Chinese national application number is 202080066349.9, the application date is October 28, 2020, and the name of the invention is "Lithium-ion secondary battery and its manufacturing method, and solid electrolyte membrane for lithium-ion secondary battery and its manufacturing method". Technical Field

[0002] The invention relates to a semi-solid lithium ion secondary battery. Background Art

[0003] A lithium-ion secondary battery is a storage battery having a negative electrode, a positive electrode, and an electrolyte sandwiched between the negative electrode and the positive electrode, and capable of charging and discharging by moving lithium ions back and forth between the two electrodes. Organic electrolytes have always been used as electrolytes in lithium-ion secondary batteries. In addition, in order to further improve reliability and safety, all-solid-state secondary batteries that use non-flammable inorganic solid electrolytes instead of organic electrolytes are being developed. In an all-solid-state secondary battery, the negative electrode, electrolyte, and positive electrode are all made of solids, which can greatly improve the safety and reliability of batteries using organic electrolytes, and can extend the life of the battery.

[0004] When a lithium-ion secondary battery is charged, electrons move from the positive electrode to the negative electrode, and lithium ions are released from the lithium oxide etc. constituting the positive electrode. The lithium ions reach the negative electrode through the electrolyte and are stored in the negative electrode. In this way, a part of the lithium ions stored in the negative electrode will absorb electrons and precipitate as metallic lithium. If the precipitate of the metallic lithium grows into a dendrite shape through repeated charging and discharging, it will eventually reach the positive electrode, causing an internal short circuit and causing it to be unable to function as a secondary battery. The dendrites (Li dendrites) are very thin, which is a problem not only in lithium-ion secondary batteries using organic electrolytes, but also in all-solid-state secondary batteries using solids as electrolytes. That is, Li dendrites can grow through the tiny gaps between solid particles constituting the solid electrolyte layer, such as cracks and pinholes, generated in the solid electrolyte layer.

[0005] Patent document 1, which aims to solve the problem of internal short circuit caused by dendrites, describes the use of capillary phenomenon to make hot melts of electronic insulating materials such as sulfur and modified sulfur remain in the gaps between inorganic solid electrolyte materials generated when the solid electrolyte layer of an all-solid-state secondary battery is formed from inorganic solid electrolyte materials, and then the hot melt is solidified by cooling. As a result, the gaps between the inorganic solid electrolyte materials can be filled with the hot melt solidified product of the electronic insulating material, and the blocking function of the dendrites based on the solid electrolyte layer can be enhanced.

[0006] Previous technical literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2018 / 164051 Summary of the invention

[0009] Technical issues to be solved by the invention

[0010] According to the technology described in Patent Document 1, the gaps between solid particles of the solid electrolyte layer can be seamlessly filled with an electronic insulating material, thereby preventing the growth of Li dendrites and obtaining an all-solid-state secondary battery with excellent charge and discharge cycle characteristics.

[0011] The inventors further studied the technology described in Patent Document 1 and found that the technology can effectively suppress the internal short circuit caused by the growth of Li dendrites. On the other hand, the battery tends to be easily high-resistance. Although the reason is not clear, it can be considered that the electronic insulating material filled in the gaps between the inorganic solid electrolyte particles inhibits the lithium ion conduction between the inorganic solid electrolyte particles connected in the thickness direction.

[0012] An object of the present invention is to provide a lithium ion secondary battery having excellent charge and discharge cycle characteristics and excellent ion conductivity, and a method for producing the same.

[0013] Furthermore, the object of the present invention is to provide a solid electrolyte membrane and a method for manufacturing the same, which can be used as a positive and negative electrode separation membrane (separator) to insulate the positive and negative electrodes of a lithium-ion secondary battery, so that the obtained lithium-ion secondary battery has excellent charge and discharge cycle characteristics and excellent ion conductivity.

[0014] Means for solving technical problems

[0015] The above-mentioned problems of the present invention are solved by the following means.

[0016] [1]

[0017] A lithium ion secondary battery having:

[0018] A solid electrolyte membrane comprising electronically insulating inorganic particles having a particle size of 10 to 500 nm, inorganic solid electrolyte particles having a particle size larger than the electronically insulating inorganic particles and having electrolyte resistance and ion conductivity, and a hot melt solidified product of an electronically insulating material that fills the gaps between the particles and is solid at 100° C. and hot melts in a temperature range of 200° C. or less;

[0019] a positive electrode layer disposed on one side of the solid electrolyte membrane; and

[0020] a negative electrode layer disposed on the side of the solid electrolyte membrane opposite to the side on which the positive electrode layer is disposed,

[0021] The heat-melted solidified product of the electronic insulating material is in an amorphous state.

[0022] The thickness of the solid electrolyte membrane is greater than or equal to [the particle size of the inorganic solid electrolyte particles×0.7] and less than or equal to [the particle size of the inorganic solid electrolyte particles×1.3].

[0023] [2]

[0024] The lithium ion secondary battery according to [1], wherein

[0025] The positive electrode active material layer constituting the positive electrode layer contains an electrolyte solution, and the thickness of the positive electrode active material layer is 200 to 2000 μm.

[0026] 〔3〕

[0027] The lithium ion secondary battery according to [1] or [2], wherein

[0028] The negative electrode active material constituting the negative electrode layer includes metallic lithium.

[0029] [4]

[0030] The lithium ion secondary battery according to any one of [1] to [3], wherein

[0031] The negative electrode layer is entirely composed of a metal lithium layer, and has a sulfide-based inorganic solid electrolyte layer between the metal lithium layer and the solid electrolyte membrane.

[0032] 〔5〕

[0033] The lithium ion secondary battery according to [1] or [2], wherein

[0034] The negative electrode active material layer constituting the negative electrode layer contains an electrolyte solution.

[0035] [6]

[0036] The lithium ion secondary battery according to [1], wherein

[0037] The above-mentioned lithium-ion secondary battery is an all-solid-state lithium-ion secondary battery.

[0038] 〔7〕

[0039] The lithium ion secondary battery according to any one of [1] to [7], wherein

[0040] The electronically insulating material includes sulfur.

[0041] [8]

[0042] The lithium ion secondary battery according to [7], wherein

[0043] The electronically insulating material is at least one of sulfur and modified sulfur.

[0044] 〔9〕

[0045] The lithium ion secondary battery according to any one of [1] to [8], wherein

[0046] The particle size of the electron insulating inorganic particles and the particle size of the inorganic solid electrolyte particles satisfy the following formula.

[0047] 5≤[particle size of inorganic solid electrolyte particles] / [particle size of electronically insulating inorganic particles]

[0048] 〔10〕

[0049] A solid electrolyte membrane for a lithium-ion secondary battery, comprising:

[0050] Electronically insulating inorganic particles having a particle size of 10 to 500 nm; inorganic solid electrolyte particles having a particle size larger than the above-mentioned electronically insulating inorganic particles and having electrolyte resistance and ion conductivity; and a hot melt solidified product of an electronically insulating material, which fills the gaps between the above-mentioned particles and is solid at 100° C. and hot melts in a temperature range of 200° C. or less,

[0051] The heat-melted solidified product of the electronic insulating material is in an amorphous state.

[0052] The thickness is greater than or equal to [the particle size of the inorganic solid electrolyte particles×0.7] and less than or equal to [the particle size of the inorganic solid electrolyte particles×1.3].

[0053]

[11]

[0054] The solid electrolyte membrane for lithium ion secondary battery according to

[10] , wherein

[0055] The electronically insulating material includes sulfur.

[0056]

[12]

[0057] The solid electrolyte membrane for lithium ion secondary batteries according to

[11] , wherein

[0058] The electronically insulating material is at least one of sulfur and modified sulfur.

[0059] 〔13〕

[0060] A method for manufacturing a solid electrolyte membrane for a lithium ion secondary battery, which is the method for manufacturing a solid electrolyte membrane for a lithium ion secondary battery described in any one of

[10] to

[12] , the method comprising the steps of forming a layer of the above-mentioned electronic insulating material in a hot-melt state using a composition, and solidifying the hot-melt of the above-mentioned electronic insulating material under a pressure of 100 MPa or more, the composition comprising: electronic insulating inorganic particles having a particle size of 10 to 500 nm; inorganic solid electrolyte particles having a particle size larger than the above-mentioned electronic insulating inorganic particles and having electrolyte resistance and Li ion conductivity; and electronic insulating material that is solid at 100°C and hot-melts in a temperature range below 200°C.

[0061]

[14]

[0062] A method for producing a lithium ion secondary battery, comprising the step of disposing the solid electrolyte membrane for a lithium ion secondary battery described in any one of

[10] to

[12] between a positive electrode and a negative electrode.

[0063] In the present specification, a numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as the lower limit and the upper limit.

[0064] Effects of the Invention

[0065] The lithium-ion secondary battery of the present invention has excellent charge-discharge cycle characteristics and excellent ion conductivity. In addition, the solid electrolyte membrane for lithium-ion secondary batteries of the present invention is used as a positive-negative electrode separation membrane for insulating the positive and negative electrodes of the lithium-ion secondary battery, so that the obtained lithium-ion secondary battery has excellent charge-discharge cycle characteristics and excellent ion conductivity.

[0066] Furthermore, according to the method for manufacturing a lithium-ion secondary battery of the present invention, a lithium-ion secondary battery having excellent charge-discharge cycle characteristics and excellent ion conductivity can be obtained. Furthermore, according to the method for manufacturing a solid electrolyte membrane for a lithium-ion secondary battery of the present invention, a solid electrolyte membrane can be obtained that can be used as a positive-negative electrode separation membrane for insulating the positive and negative electrodes of the lithium-ion secondary battery, so that the obtained lithium-ion secondary battery has excellent charge-discharge cycle characteristics and excellent ion conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0067] Figure 1 It is a longitudinal sectional view schematically showing the basic structure of an all-solid lithium ion secondary battery which is one embodiment of the lithium ion secondary battery.

[0068] Figure 2 This is a longitudinal cross-sectional view schematically showing a preferred stacking form of the lithium ion secondary battery of the present invention.

[0069] Figure 3This is a longitudinal sectional view schematically showing another preferred stacking form of the lithium ion secondary battery of the present invention.

[0070] Figure 4 This is a longitudinal sectional view schematically showing another preferred stacking form of the lithium ion secondary battery of the present invention.

[0071] Figure 5 This is a longitudinal sectional view schematically showing another preferred stacking form of the lithium ion secondary battery of the present invention.

[0072] Figure 6 This is a longitudinal sectional view schematically showing another preferred stacking form of the lithium ion secondary battery of the present invention.

[0073] Figure 7 This is a longitudinal sectional view schematically showing another preferred stacking form of the lithium ion secondary battery of the present invention. DETAILED DESCRIPTION

[0074] [Lithium-ion secondary battery]

[0075] First, Figure 1 The operating mechanism of a general lithium ion (Li ion) secondary battery will be described by taking the embodiment of the all-solid-state Li ion secondary battery shown as an example. Figure 1 This is a cross-sectional view schematically showing a general layer structure of an all-solid-state Li-ion secondary battery which is one embodiment of a Li-ion secondary battery. Figure 1 The all-solid-state Li-ion secondary battery 10 shown has a structure in which a negative electrode collector 1, a negative electrode active material layer 2 (the negative electrode collector 1 and the negative electrode active material layer 2 are collectively referred to as the negative electrode layer), a solid electrolyte layer 3, a positive electrode active material layer 4 and a positive electrode collector 5 (the positive electrode active material layer 4 and the positive electrode collector 5 are collectively referred to as the positive electrode layer) are stacked in sequence when viewed from the negative electrode side, and adjacent layers are in direct contact with each other. By adopting this structure, electrons (e) are supplied from the positive electrode side to the negative electrode side via the circuit wiring 7 during charging. - ), Li ions are released from the positive electrode active material layer 4, and the Li ions move toward the negative electrode side through the (Li ion conduction) solid electrolyte layer 3 and are accumulated in the negative electrode active material layer 2.

[0076] On the other hand, during discharge, the Li ions accumulated in the negative electrode active material layer 2 are released, and the Li ions return to the positive electrode side through the solid electrolyte layer 3 and are accumulated in the positive electrode active material layer 4. At this time, electrons move from the negative electrode side to the positive electrode side via the circuit wiring 7, thereby supplying electrons to the working part 6. In the all-solid-state Li ion secondary battery 10 shown in the figure, a light bulb is used as the working part 6, and the light bulb is lit by discharge.

[0077] Furthermore, the all-solid-state Li ion secondary battery can also be configured to have no negative electrode active material layer 2, and the solid electrolyte layer 3 is in direct contact with the negative electrode collector 1. In the all-solid-state Li ion secondary battery of this mode, a part of the Li ions accumulated in the negative electrode during charging is combined with electrons to precipitate as metallic lithium (metallic Li) on the surface of the negative electrode collector. That is, the all-solid-state secondary battery of this mode makes the metallic Li precipitated on the surface of the negative electrode act as a negative electrode active material layer. For example, it is said that metallic Li has a theoretical capacity that is more than 10 times that of graphite, which is widely used as a negative electrode active material. Therefore, by setting the metallic Li to precipitate on the negative electrode and pressing the solid electrolyte layer on the precipitated metallic Li, a layer of metallic lithium can be formed on the surface of the collector, thereby enabling a secondary battery with a high energy density.

[0078] Furthermore, since the thickness of the all-solid-state secondary battery is thinner in the form of removing the negative electrode active material layer, when the battery is wound into a roll, there is also an advantage that the occurrence of cracks in the solid electrolyte layer can be further suppressed.

[0079] In addition, in this specification, an all-solid-state Li-ion secondary battery without a negative electrode active material layer means that no negative electrode active material layer is formed in the layer formation process in battery manufacturing, and as described above, a negative electrode active material layer is formed between the solid electrolyte layer and the negative electrode collector by charging (repeated charge and discharge).

[0080] Furthermore, the all-solid-state Li-ion secondary battery can also be configured such that a metal lithium layer such as a lithium foil performs both the functions of a negative electrode current collector and a negative electrode active material layer. That is, the negative electrode layer can be configured as a single metal lithium layer.

[0081] Taking an all-solid-state Li secondary battery as an example, the layer structure and working mechanism of the above-mentioned general Li ion secondary battery are described. In the above-mentioned method, the solid electrolyte layer 3 has Li ion conductivity and acts as a positive and negative electrode separation membrane (separator) that insulates the positive and negative electrodes of the Li ion secondary battery.

[0082] Next, preferred embodiments of the Li ion secondary battery of the present invention will be described.

[0083] The Li ion secondary battery of the present invention has a characteristic in the structure of the separator. That is, the Li ion secondary battery of the present invention uses a solid electrolyte membrane having a specific structure as a separator.

[0084] Here, the Li ion secondary battery of the present invention is not limited to an all-solid-state Li ion secondary battery as long as it is a solid electrolyte membrane composed of a specific material combination specified in the present invention and having a specific thickness specified in the present invention as a separator, and can also be a Li ion secondary battery using an electrolyte (electrolyte Li ion secondary battery). In the present invention, "electrolyte Li ion secondary battery" widely includes secondary batteries using electrolytes. For example, a so-called semi-solid battery in which an electrolyte and an electrode active material (positive electrode active material or negative electrode active material) are mixed to prepare a viscous slurry, and a semi-solid electrode active material layer (positive electrode active material layer or negative electrode active material layer) is thickly coated to form a semi-solid electrode active material layer (positive electrode active material layer or negative electrode active material layer) is also included in the "electrolyte secondary battery" of the present invention. The formation of such a semi-solid electrode is well known in itself, for example, it can be referred to Japanese Patent Table 2016-511521 Gazette. The semi-solid electrode active material layer can be thickened, which is advantageous in the high energy density of the battery. The thickness of the semi-solid electrode active material layer can be set to about 200 to 2000 μm, for example.

[0085] In the Li ion secondary battery of the present invention, one of the positive electrode active material layer and the negative electrode active material layer preferably contains an electrolyte (preferably a semi-solid electrode) and the other does not contain an electrolyte (an all-solid electrode).

[0086] Furthermore, the positive electrode active material layer may be configured to include an electrolyte, or may be configured to not include a negative electrode active material layer. In this case, as described above, a negative electrode active material layer formed of metal Li may be formed between the solid electrolyte layer and the negative electrode current collector by charging. Furthermore, it is also preferred that the negative electrode layer be composed of metal Li.

[0087] The materials, electrolytes, components or laminated structures of the Li ion secondary batteries of the present invention, components, and methods for manufacturing Li ion secondary batteries are not particularly limited except for the structure of the solid electrolyte membrane used as a separator. These materials, electrolytes, components, etc. can be appropriately applied to materials, electrolytes, components, etc. used in conventional Li ion secondary batteries. In addition, for the method for making the Li ion secondary battery of the present invention, in addition to the structure of the solid electrolyte membrane used as a separator, conventional methods can also be appropriately adopted. For example, reference can be made to International Publication No. 2018 / 164051, Japanese Patent Publication No. 2016-201308, Japanese Patent Publication No. 2019-12688, etc.

[0088] The solid electrolyte membrane which is a characteristic structure of the Li-ion secondary battery of the present invention is described below. Hereinafter, this solid electrolyte membrane is also referred to as "the solid electrolyte membrane of the present invention."

[0089] <Solid electrolyte membrane (separator)>

[0090] One embodiment of the solid electrolyte membrane of the present invention comprises electronically insulating inorganic particles, inorganic solid electrolyte particles having both electrolyte resistance and Li ion conductivity, and a thermally molten solid of an electronically insulating material filling spaces between the particles and having a thermal melting temperature within a specific temperature range.

[0091] The “electronically insulating inorganic particles,” “inorganic solid electrolyte particles,” and “electronically insulating material” included in the solid electrolyte membrane of the present invention are preferably composed of different materials.

[0092] The particle size of the “electronically insulating inorganic particles” in the solid electrolyte membrane of the present invention is 10 to 500 nm, and the particle size of the “inorganic solid electrolyte particles” is larger than that of the “electronically insulating inorganic particles”.

[0093] The thickness of the solid electrolyte membrane of the present invention is greater than [the particle size of the above-mentioned inorganic solid electrolyte particles × 0.7] and less than [the particle size of the above-mentioned inorganic solid electrolyte particles × 1.3]. That is, in the solid electrolyte membrane of the present invention, the above-mentioned inorganic solid electrolyte particles are substantially arranged in a single layer (one layer) in the surface direction. Therefore, the Li ion secondary battery in which the solid electrolyte layer is arranged as a separator can complete the Li ion conduction in the thickness direction of the solid electrolyte layer by ion conduction within a single particle. Therefore, the resistance of the battery can be suppressed to a low level.

[0094] Furthermore, the solid electrolyte membrane of the present invention is in a state where the gaps between the inorganic solid electrolyte particles are filled with electronically insulating inorganic particles having a smaller particle size than the inorganic solid electrolyte particles and a hot melt coagulation of an electronically insulating material. Therefore, although the inorganic solid electrolyte particles are thin layers substantially arranged in a single layer (one layer) in the surface direction, by being used as a separator for a Li ion secondary battery, a Li ion secondary battery that can fully block the growth of Li dendrites and has excellent charge and discharge cycle characteristics can be provided.

[0095] The materials for forming the solid electrolyte membrane of the present invention will be described in sequence.

[0096] -Electronically insulating inorganic particles-

[0097] The particle size of the electronically insulating inorganic particles contained in the solid electrolyte membrane of the present invention is 10 to 500 nm, which is smaller than that of the inorganic solid electrolyte particles. Therefore, the electronically insulating inorganic particles can enter the gaps between the inorganic solid electrolytes. In addition, when the electronically insulating inorganic particles enter the gaps between the inorganic solid electrolytes, when the electronically insulating material is heat-melted, the hot melt easily moves to the gaps between the solid particles due to the capillary phenomenon, and the gaps between the solid particles can be fully filled without gaps through the hot melt of the electronically insulating material. In addition, when the hot melt is cooled (when released from the heated state), the electronically insulating inorganic particles limit the movement of the hot melt by their cohesive force, etc., and can inhibit the crystallization of the hot melt (maintain a specified non-crystalline state). That is, in the solidified material (hot melt solidified material) obtained by cooling after hot melting, the generation of tiny pores through which Li dendrites can penetrate can also be suppressed. By melting and solidifying the electronic insulating material under high pressure (e.g., 100 MPa or more, preferably 140 MPa or more, more preferably 160 MPa or more, further preferably 200 MPa or more, and usually 1000 MPa or less), the hot melt can better maintain the amorphous state and solidify. In addition, the electronic insulating inorganic particles themselves also have the effect of preventing the growth of dendrites.

[0098] The electronically insulating inorganic particles generally do not have lithium ion conductivity. In the solid electrolyte membrane of the present invention, it is the inorganic solid electrolyte particles that are essentially responsible for the Li ion conductivity. However, within the scope of not impairing the effect of the present invention, the electronically insulating inorganic particles may have lithium ion conductivity. That is, if the particle size of the electronically insulating inorganic particles is 10 to 500 nm, they may have Li ion conductivity, and their cohesive force may suppress crystallization during solidification of the hot melt. If the electronically insulating inorganic particles and the inorganic solid electrolyte particles have the same composition, the selection of the slurry solvent becomes easy and the cost can be reduced.

[0099] In this specification, the term "solid particles" in the solid electrolyte membrane is used to refer to both inorganic solid electrolyte particles and electronically insulating inorganic particles.

[0100] In the present invention, "the hot melt solidified product of the electronic insulating material is in an amorphous state" can be determined by micro-Raman spectroscopy. Specifically, it can be determined whether it is in an amorphous state by observing the sample surface with a resolution of 3 μm using a micro-Raman spectroscopy device. For example, when the electronic insulating material is sulfur, the bandwidth of the Raman shift detected in crystalline sulfur is 3.8 to 4.0 cm -1 There is a peak at , but the bandwidth is 4.5 to 5.2 cm in amorphous sulfur -1 Therefore, when the bandwidth of Raman shift is 4.5~5.2cm -1When the electron insulating material is not sulfur, it can be determined whether it is in an amorphous state by checking the bandwidth where the peak exists in the crystalline state and the bandwidth where the peak exists in the amorphous state.

[0101] The particle size of the electron-insulating inorganic particles is preferably 15 to 400 nm, more preferably 20 to 300 nm, further preferably 20 to 200 nm, further preferably 25 to 150 nm, and particularly preferably 25 to 100 nm.

[0102] The relationship between the particle sizes of the electron insulating inorganic particles and the inorganic solid electrolyte particles described in detail later is preferably [particle size of the inorganic solid electrolyte particles] / [particle size of the electron insulating inorganic particles]≥5, and more preferably [particle size of the inorganic solid electrolyte particles] / [particle size of the electron insulating inorganic particles]≥10.

[0103] The relationship between the particle sizes of the electronically insulating inorganic particles and the inorganic solid electrolyte particles is preferably 5≤[particle size of the inorganic solid electrolyte particles] / [particle size of the electronically insulating inorganic particles]≤10000, more preferably 5≤[particle size of the inorganic solid electrolyte particles] / [particle size of the electronically insulating inorganic particles]≤8000, more preferably 5≤[particle size of the inorganic solid electrolyte particles] / [particle size of the electronically insulating inorganic particles]≤6000, more preferably 5≤[particle size of the inorganic solid electrolyte particles] / [particle size of the electronically insulating inorganic particles]≤4000, more preferably 5≤[particle size of the inorganic solid electrolyte particles] / [particle size of the electronically insulating inorganic particles]≤ [particle size of the inorganic solid electrolyte particles] / [particle size of the electronically insulating inorganic particles]≤2000, more preferably 5≤[particle size of the inorganic solid electrolyte particles] / [particle size of the electronically insulating inorganic particles]≤1000, more preferably 10≤[particle size of the inorganic solid electrolyte particles] / [particle size of the electronically insulating inorganic particles]≤600, more preferably 10≤[particle size of the inorganic solid electrolyte particles] / [particle size of the electronically insulating inorganic particles]≤400, and preferably 20≤[particle size of the inorganic solid electrolyte particles] / [particle size of the electronically insulating inorganic particles]≤300, and preferably 20≤[particle size of the inorganic solid electrolyte particles] / [particle size of the electronically insulating inorganic particles]≤200.

[0104] In the present invention, the "particle size" refers to an average primary particle size. The average primary particle size is a volume-based median diameter (d50).

[0105] The constituent material of the electronically insulating inorganic particles is not particularly limited as long as it is an inorganic particle having electronic insulating properties. In the present invention, "electronic insulating properties" means that the electronic conductivity is 10 at a measurement temperature of 25°C. -9S / cm or less. Examples of electronically insulating inorganic particles include aluminum oxide, silicon oxide, boron nitride, cerium oxide, diamond, zeolite, etc., but the present invention is not limited thereto. The electronically insulating inorganic particles are preferably metal oxides, and aluminum oxide is preferably used from the viewpoint of being able to produce microparticles of about 50 nm with high purity and low cost.

[0106] In the solid electrolyte membrane of the present invention, the content of the electron insulating inorganic particles is preferably 5 to 45% by volume, more preferably 10 to 40% by volume, and even more preferably 20 to 30% by volume.

[0107] -Inorganic solid electrolyte particles-

[0108] The inorganic solid electrolyte particles contained in the solid electrolyte membrane of the present invention are Li ion conductive inorganic particles composed of a material different from the electronic insulating inorganic particles. As described above, the particle size is larger than the electronic insulating inorganic particles. The particle size of the inorganic solid electrolyte particles is preferably 0.1 μm or more, and is preferably 0.5 μm or more. In addition, the particle size is usually 200 μm or less, and is preferably 100 μm or less.

[0109] Specifically, the preferred range of the particle size of the inorganic solid electrolyte particles is preferably 0.1 to 200 μm, more preferably 0.2 to 100 μm, further preferably 0.4 to 80 μm, further preferably 0.8 to 50 μm, further preferably 1 to 40 μm, further preferably 1 to 30 μm, and further preferably 1 to 20 μm.

[0110] Furthermore, the inorganic solid electrolyte particles preferably have electrolyte tolerance. Since the inorganic solid electrolyte particles have electrolyte tolerance, even if used as a separator of a Li-ion secondary battery having an electrolyte in the positive electrode layer or the negative electrode layer, the inorganic solid electrolyte particles are not prone to side reactions, decomposition, etc. As such inorganic solid electrolyte particles, particles of oxide-based inorganic solid electrolytes described below can be preferably applied. Oxide-based inorganic solid electrolytes themselves are well known and are widely used as solid electrolytes for all-solid-state secondary batteries.

[0111] (Sulfide-based inorganic solid electrolyte)

[0112] The oxide-based inorganic solid electrolyte contains oxygen atoms (O) and has Li ion conductivity. The oxide-based inorganic solid electrolyte is preferably an electron insulating compound.

[0113] As specific examples of compounds, for example, Li xa La ya TiO3 [xa=0.3~0.7, ya=0.3~0.7] (LLT), Li xb Layb Zr zb M bb mb O nb (M bb is at least one element selected from the group consisting of Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In, and Sn, xb satisfies 5≤xb≤10, yb satisfies 1≤yb≤4, zb satisfies 1≤zb≤4, mb satisfies 0≤mb≤2, and nb satisfies 5≤nb≤20. ), Li xc B yc M cc zc O nc (M cc is at least one element selected from C, S, Al, Si, Ga, Ge, In, and Sn, xc satisfies 0≤xc≤5, yc satisfies 0≤yc≤1, zc satisfies 0≤zc≤1, and nc satisfies 0≤nc≤6. ), Li xd (Al, Ga) yd (Ti, Ge) zd Si ad P md O nd (where 1≤xd≤3, 0≤yd≤1, 0≤zd≤2, 0≤ad≤1, 1≤md≤7, 3≤nd≤13), Li (3-2xe) M ee xe D ee O(xe represents an integer greater than or equal to 0 and less than or equal to 0.1, M ee Represents a divalent metal atom. ee represents a halogen atom or a combination of two or more halogen atoms. ), Li xf Si yf O zf (1≤xf≤5, 0<yf≤3, 1≤zf≤10), Li xg S yg O zg (1≤xg≤3, 0<yg≤2, 1≤zg≤10), Li3BO3-Li2SO4, Li2O-B2O3-P2O5, Li2O-SiO2, Li6BaLa2Ta2O 12 、Li3PO (4-3 / 2w) N w (w satisfies w<1), Li with LISICON (Lithium super ionic conductor) type crystal structure 3.5 Zn 0.25 GeO4, La with perovskite crystal structure 0.55 Li 0.35TiO3, LiTi2P3O with NASICON (Natrium superionic conductor) type crystal structure 12 , Li 1+xh+yh (Al, Ga) xh (Ti, Ge) 2-xh Si yh P 3-yh O 12 (where 0≤xh≤1, 0≤yh≤1), Li7La3Zr2O with garnet crystal structure 12 (LLZ) etc. Furthermore, phosphorus compounds containing Li, P and O are also preferred. For example, lithium phosphate (Li3PO4), LiPON in which a part of oxygen in lithium phosphate is substituted with nitrogen, LiPOD 1 (D 1 is at least one selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt, Au, etc. In addition, LiA 1 ON(A 1 is at least one selected from Si, B, Ge, Al, C, Ga, etc.) and the like.

[0114] In the solid electrolyte membrane of the present invention, the content of the inorganic solid electrolyte particles is preferably 10 to 90% by volume, more preferably 20 to 80% by volume, further preferably 30 to 70% by volume, and further preferably 40 to 60% by volume.

[0115] -Hot-melted solidified product of electronic insulating material-

[0116] The solid electrolyte membrane of the present invention contains a hot melt solidified product of an electronic insulating material. The gaps between the solid particles contained in the solid electrolyte membrane of the present invention are in a state of being filled with the hot melt solidified product of the electronic insulating material. "In a state of being filled with the hot melt solidified product of the electronic insulating material" means that there is substantially no gap of electronic insulating material in the gaps between the solid particles along the shape between the solid particles, and the electronic insulating material present in the gaps between the solid particles has a hot melting history (cooled and solidified after hot melting). The electronic insulating material is spread in the gaps between the solid particles by capillary phenomena and / or pressure in a hot melt state, and by solidifying in this state, the gaps between the solid particles can be filled with the hot melt solidified product of the electronic insulating material.

[0117] As the above-mentioned electronic insulating material, a material having the property of being solid at 100°C (i.e., having a melting point exceeding 100°C) and being heat-melted in a temperature range below 200°C (i.e., having a melting point below 200°C) is used. "Solid at 100°C" means being solid at 100°C under 1 atmosphere. And, "heat-melting in a temperature range below 200°C" means being heat-melted in a temperature range below 200°C under 1 atmosphere. By using such an electronic insulating material, when or after forming a layer using a mixture containing electronic insulating inorganic particles, inorganic solid electrolyte particles and electronic insulating material, it can be easily heated to a temperature at which the electronic insulating material melts, and by this heating, the molten filling material is moved to the gaps between the solid particles by capillary phenomena and / or pressure. Then, by cooling the electronic insulating material to solidify, a state of the hot-melted solidified material of the electronic insulating material being filled substantially without gaps along the shape between the solid particles can be produced.

[0118] As the electronic insulating material, it is preferred that the material is harder than the dendrite in a solid state to prevent the growth of the dendrite. For example, sulfur, modified sulfur, iodine, a mixture of sulfur and iodine, etc. can be cited, among which sulfur and / or modified sulfur can be suitably used. Sulfur that can be used as an electronic insulating material refers to monomeric sulfur (including substances existing in polymers in addition to sulfur itself).

[0119] Furthermore, modified sulfur is obtained by mixing sulfur and a modifier. For example, pure sulfur and an olefin compound as a modifying additive are mixed to obtain modified sulfur in which a part of the sulfur is modified into a sulfur polymer. Sulfur or modified sulfur exists without gaps between solid particles as a hot molten solid, thereby being able to physically block Li dendrites growing between solid particles.

[0120] In addition, a reaction between Li dendrites and sulfur may also occur through the contact between dendrites and sulfur. It is believed that when Li dendrites come into contact with sulfur, a reaction of 2Li+S→Li2S occurs, and the growth of Li dendrites stops. If this reaction occurs, the reaction product also coexists between the solid particles. Since the reaction product is an electronically insulating compound that is harder than Li dendrites, it is believed that the growth of Li dendrites can be blocked. Through the reaction between Li dendrites and sulfur, the volume of the electronically insulating material between the solid particles is expanded, and the effect of more reliably blocking the remaining gaps between the solid particles can also be expected.

[0121] In the solid electrolyte membrane of the present invention, the content of the thermally molten solidified product of the electronic insulating material is preferably 5 to 45% by volume, more preferably 10 to 40% by volume, and even more preferably 20 to 30% by volume.

[0122] The solid electrolyte membrane of the present invention may contain an organic binder between solid particles. As such an organic binder, an organic binder generally used in a solid electrolyte layer of a secondary battery can be appropriately used.

[0123] <Manufacturing of solid electrolyte membrane (separator)>

[0124] The method for producing the solid electrolyte membrane of the present invention is not particularly limited as long as a solid electrolyte membrane that satisfies the requirements of the present invention can be obtained. An example of the method for producing the solid electrolyte membrane of the present invention is described below.

[0125] At least the electronic insulating inorganic particles, the inorganic solid electrolyte particles and the electronic insulating material are kneaded to prepare a composition. The kneading is preferably set to a temperature above the heat melting temperature of the electronic insulating material. Then, the kneaded product is stretched with a roller press or the like at a temperature above the heat melting temperature of the electronic insulating material to form a thin layer sheet of the thickness specified in the present invention. Then, by cooling, the electronic insulating material solidifies from a hot melt state, and a solid electrolyte membrane in a state where the hot melt solidified product of the electronic insulating material is filled between the solid particles can be obtained.

[0126] The electronic insulating material is preferably solidified from the hot melt state under pressure. For example, under pressure of more than 100MPa (preferably more than 140MPa, more preferably more than 160MPa, more preferably more than 200MPa, usually less than 1000MPa), the hot melt of the electronic insulating material is cooled and solidified, so that it can be solidified under the state of fully maintaining the amorphous state of the hot melted electronic insulating material. That is, the crystallization of the hot melt solidified material of the electronic insulating material filling the gaps between the solid particles can be suppressed, and the generation of tiny gaps that may become channels such as Li dendrites and electrolytes can also be effectively suppressed.

[0127] The thickness of the solid electrolyte membrane thus obtained is greater than [particle size of the inorganic solid electrolyte particles × 0.7] and less than [particle size of the inorganic solid electrolyte particles × 1.3]. In addition, even if the thickness of the solid electrolyte membrane is greater than the particle size of the inorganic solid electrolyte particles, the "particle size" is the average primary particle size as described above, so as long as the particle size of the inorganic solid electrolyte particles is less than × 1.3, a sufficient number of inorganic solid electrolyte particles can be in contact with both the positive electrode and the negative electrode with one particle. As a result, Li ion conduction can be smoothly performed.

[0128] From the viewpoint of further improving Li ion conductivity, the thickness of the solid electrolyte membrane is preferably less than [particle size of the inorganic solid electrolyte particles × 1.2], and is further preferably less than [particle size of the inorganic solid electrolyte particles × 1.15], and is further preferably less than [particle size of the inorganic solid electrolyte particles × 1.1], and is further preferably less than [particle size of the inorganic solid electrolyte particles × 1.0].

[0129] In the present invention, the thickness of the solid electrolyte membrane is a value obtained by measuring the thickness at 50 locations at 10 μm intervals with respect to the cross section of the solid electrolyte membrane and arithmetically averaging the thicknesses. The thickness can be measured by observing the cross section of the solid electrolyte membrane with a scanning electron microscope (SEM).

[0130] <Layer structure of lithium-ion secondary battery>

[0131] As long as the Li-ion secondary battery of the present invention has the solid electrolyte membrane of the present invention as a separator, it includes various battery modes as described above. The preferred embodiment of the Li-ion secondary battery of the present invention is described with reference to the accompanying drawings. In addition, in the drawings mentioned below, the positive electrode collector and the negative electrode collector are omitted unless otherwise specified. In addition, each of the drawings is a schematic diagram for facilitating the understanding of the present invention, and the size or relative size relationship of each component is sometimes changed for the sake of convenience of explanation, and does not directly represent the actual relationship. In addition, except for the matters specified in the present invention, it is not limited to the appearance and shape shown in these drawings.

[0132] -Implementation Method-1-

[0133] exist Figure 2 In the Li ion secondary battery of the embodiment-1 shown, a semi-solid positive electrode active material layer 21 containing an electrolyte is used as a positive electrode active material layer. The solid electrolyte membrane 22 of the present invention containing inorganic solid electrolyte particles 25, electronic insulating inorganic particles 26 and a hot melt solidified product 27 of an electronic insulating material is provided in contact with the semi-solid positive electrode active material layer 21, and a solid electrolyte layer 23 containing sulfide-based inorganic solid electrolyte particles is stacked in contact with the solid electrolyte membrane 22. Compared with the oxide-based inorganic solid electrolyte, the sulfide-based inorganic solid electrolyte has a smaller lithium ion capture effect and a higher Li ion conductivity. On the other hand, the sulfide-based inorganic solid electrolyte produces a side reaction when in contact with the electrolyte, and is easily decomposed.

[0134] In Embodiment-1, a metal Li negative electrode 24 is provided on a solid electrolyte layer 23. By providing a solid electrolyte layer 23 between the metal lithium negative electrode 24 and the solid electrolyte membrane 22, a battery having low contact resistance with the metal Li negative electrode and excellent Li dendrite resistance can be obtained.

[0135] The solid electrolyte layer 23 may contain various components that may be contained in a solid electrolyte layer of a conventional all-solid-state secondary battery in addition to the sulfide-based inorganic solid electrolyte particles. For example, organic binders such as organic polymers, ion conductive additives, etc. may be cited. In addition, it may be configured such that the hot melt solidified material of the electronic insulating material is filled between the solid particles of the solid electrolyte layer 23 in the same manner as the solid electrolyte membrane 22.

[0136] In this embodiment-1, as described above, a semi-solid positive electrode active material layer 21 containing an electrolyte is used. On the other hand, the inorganic solid electrolyte particles 25 constituting the solid electrolyte membrane 22 in contact with the semi-solid positive electrode active material layer 21 are composed of an oxide-based inorganic solid electrolyte with electrolyte resistance. Therefore, it is possible to set the solid electrolyte membrane 22 to be directly stacked on the semi-solid positive electrode active material layer 21. In addition, in the solid electrolyte membrane 22, the gaps between the solid particles are filled with a hot melt solidified product 27 of an electronic insulating material without gaps, and the crystallization of the solidified product 27 is also suppressed. Therefore, it is possible to more reliably prevent the electrolyte from penetrating from the semi-solid positive electrode active material layer 21 to the negative electrode side, and to prevent the side reaction of the sulfide-based inorganic solid electrolyte and the electrolyte constituting the solid electrolyte layer 23 above it.

[0137] Furthermore, although the solid electrolyte membrane 22 is a thin separator in which inorganic solid electrolyte particles are substantially arranged in a single layer, it can effectively block Li dendrites growing from the negative electrode.

[0138] In Embodiment-1, a semi-solid positive electrode active material layer 21 is used, which can make the positive electrode active material layer thicker. Therefore, high energy density can be achieved. In addition, the negative electrode is formed of metal Li with a large theoretical capacity, which also contributes to high energy density.

[0139] The sulfide-based inorganic solid electrolyte constituting the above-mentioned solid electrolyte layer 23 is described. The sulfide-based inorganic solid electrolyte itself is well known, and substances widely used as solid electrolytes for all-solid-state secondary batteries can be used without particular restrictions. The sulfide-based inorganic solid electrolyte is preferably a compound containing sulfur atoms (S), and having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and having electronic insulation. The sulfide-based inorganic solid electrolyte preferably contains at least Li, S and P as elements, and has lithium ion conductivity, but may also contain other elements besides Li, S and P according to the purpose.

[0140] Examples of the sulfide-based inorganic solid electrolyte include lithium ion conductive inorganic solid electrolytes satisfying a composition represented by the following formula (I).

[0141] L a1 M b1P c1 S d1 A e1 Formula (I)

[0142] In the formula, L represents an element selected from Li, Na and K, preferably Li. M represents an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al and Ge. A represents an element selected from I, Br, Cl and F. a1 to e1 represent the composition ratio of each element, and a1:b1:c1:d1:e1 satisfies 1 to 12:0 to 5:1:2 to 12:0 to 10. a1 is more preferably 1 to 9, and more preferably 1.5 to 7.5. b1 is preferably 0 to 3. d1 is more preferably 2.5 to 10, and more preferably 3.0 to 8.5. e1 is more preferably 0 to 5, and more preferably 0 to 3.

[0143] As described below, the composition ratio of each element can be controlled by adjusting the blending amount of the raw material compound when producing the sulfide-based inorganic solid electrolyte.

[0144] The sulfide-based inorganic solid electrolyte may be amorphous (glass), crystallized (glass ceramic), or only partially crystallized. For example, Li-PS-based glass containing Li, P, and S or Li-PS-based glass ceramic containing Li, P, and S may be used.

[0145] Sulfide-based inorganic solid electrolytes can be manufactured by reacting at least two or more raw materials, for example, lithium sulfide (Li2S), phosphorus sulfide (for example, phosphorus pentasulfide (P2S5)), elemental phosphorus, elemental sulfur, sodium sulfide, hydrogen sulfide, lithium halide (for example, LiI, LiBr, LiCl) and sulfides of the elements represented by the above M (for example, SiS2, SnS, GeS2).

[0146] The ratio of Li2S to P2S5 in the Li-PS glass and Li-PS glass ceramics is preferably 60:40 to 90:10, and more preferably 68:32 to 78:22, in terms of the molar ratio of Li2S:P2S5. By setting the ratio of Li2S to P2S5 to this range, the lithium ion conductivity can be improved. Specifically, the lithium ion conductivity can be preferably set to 1×10 -4 S / cm or more, more preferably 1×10 -3 S / cm or more. Although there is no specific upper limit, it is actually 1×10 -1 S / cm or less.

[0147] As specific examples of sulfide-based inorganic solid electrolytes, the combination of raw materials is shown below. For example, Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-Li2O-P2S5, Li2S-Li3PO4-P2S5, Li2S-P2S5-P2O5, Li2S-P2S5-SiS2, Li2S-P2S5-SiS2-LiCl, Li2S-P2S5-SnS, Li2S-P2S5-Al2S 3. Li2S-GeS2, Li2S-GeS2-ZnS, Li2S-Ga2S3, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Li2S-GeS2-Al2S3, Li2S-SiS2, L i2S-Al2S3, Li2S-SiS2-Al2S3, Li2S-SiS2-P2S5, Li2S-SiS2-P2S5-LiI, Li2S-SiS2-LiI, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li 10 GeP2S 12 etc. Among them, the mixing ratio of each raw material is not limited. As a method for synthesizing a sulfide-based inorganic solid electrolyte material using such a raw material composition, for example, an amorphization method can be cited. As an amorphization method, for example, a mechanical polishing method, a solution method, and a melt quenching method can be cited. It is possible to perform treatment at room temperature, thereby simplifying the manufacturing process.

[0148] -Implementation Method-2-

[0149] exist Figure 3 In the Li ion secondary battery of the embodiment-2 shown, the semi-solid positive electrode active material layer 31 and the solid electrolyte membrane 32 are respectively the same as the semi-solid positive electrode active material layer 21 and the solid electrolyte membrane 22 of the embodiment-1. In this embodiment-2, a semi-solid negative electrode active material layer 33 containing an electrolyte is arranged on the negative electrode side in contact with the solid electrolyte membrane 32.

[0150] In Embodiment-2, although the solid electrolyte membrane of the present invention is arranged as a separator between the positive and negative electrodes, and the inorganic solid electrolyte particles are substantially arranged as a thin single-layer separator, it can also effectively block Li dendrites growing from the negative electrode.

[0151] In Embodiment-2, a semi-solid positive electrode active material layer 31 and a semi-solid negative electrode active material layer 33 are used, and the two electrode active material layers can be thickened. Therefore, a high energy density can be achieved. In addition, the electrolyte of the semi-solid positive electrode active material layer 31 and the electrolyte of the semi-solid negative electrode active material layer 33 are separated by the solid electrolyte membrane 32 and do not cross each other. Therefore, the electrolyte of the semi-solid positive electrode active material layer 31 and the electrolyte of the semi-solid negative electrode active material layer 33 can be set to different electrolytes. As a result, the range of selection of active materials for the positive and negative electrodes is expanded.

[0152] -Implementation Method-3-

[0153] Figure 4 The embodiment-3 shown is a so-called all-solid-state Li-ion secondary battery. The solid electrolyte membrane 42 of the present invention is arranged as an inorganic solid electrolyte layer arranged between the positive electrode active material layer 41 and the negative electrode active material layer 43. The solid electrolyte membrane 42 is the same as the solid electrolyte membrane 22 of the embodiment-1.

[0154] - Implementation Method - 4 -

[0155] Figure 5 The Li-ion secondary battery of the embodiment 4 shown in the embodiment 1 is further provided with a structure of a separator 28 between the semi-solid positive electrode active material layer 21 and the solid electrolyte membrane 22. The separator 28 can be widely used as a separator commonly used in electrolyte Li-ion secondary batteries. As constituent materials of the separator 28, for example, porous polymer materials, inorganic materials, organic-inorganic hybrid materials or glass fibers can be cited. The volume ratio occupied by the gaps in the separator 28, that is, the porosity is preferably 20% to 90%, and more preferably 35% to 80%.

[0156] Examples of the polymer material include cellulose nonwoven fabrics, polyethylene, and polypropylene, and a separator made of these materials in combination may be used. Preferably, two or more microporous membranes having different pore sizes, porosities, pore blocking temperatures, and the like are laminated.

[0157] Examples of the inorganic material include oxides such as aluminum oxide and silicon dioxide; nitrides such as aluminum nitride and silicon nitride; and sulfates such as barium sulfate and calcium sulfate.

[0158] By further configuring a separator 28 between the semi-solid positive electrode active material layer 21 and the solid electrolyte membrane 22, it is possible to prevent the positive electrode active material, the conductive aid, the hot melt solidified product (sulfur) of the electronic insulating material, etc. from coexisting in the presence of the electrolyte, and it is possible to prevent the side reaction between the positive electrode active material or the conductive aid and the hot melt solidified product (sulfur) of the electronic insulating material.

[0159] -Implementation Method-5-

[0160] Figure 6 The Li ion secondary battery of the fifth embodiment shown has a structure in which a separator 37 is further arranged between the semi-solid positive electrode active material layer 31 and the solid electrolyte membrane 32 in the second embodiment. The separator 37 is the same as the separator 28 described in the fourth embodiment.

[0161] By further configuring a separator 37 between the semi-solid positive electrode active material layer 31 and the solid electrolyte membrane 32, it is possible to prevent the positive electrode active material, the conductive aid, the hot melt solidified product (sulfur) of the electronic insulating material, etc. from coexisting in the presence of the electrolyte, and it is possible to prevent the side reaction between the positive electrode active material or the conductive aid and the hot melt solidified product (sulfur) of the electronic insulating material.

[0162] -Implementation Method-6-

[0163] Figure 7 The Li-ion secondary battery of the embodiment-6 shown in the embodiment-2 has a structure in which a separator 37 is further arranged between the semi-solid positive electrode active material layer 31 and the solid electrolyte membrane 32, and a separator 38 is also arranged between the solid electrolyte membrane 32 and the semi-solid negative electrode active material layer 33. These separators 37 and 38 are the same as the separator 28 described in the embodiment-4.

[0164] By further configuring a separator 37 between the semi-solid positive electrode active material layer 31 and the solid electrolyte membrane 32, it is possible to prevent the positive electrode active material, the conductive aid, the hot melt solidified product (sulfur) of the electronic insulating material, etc. from coexisting in the presence of the electrolyte, and it is possible to prevent the side reaction between the positive electrode active material or the conductive aid and the hot melt solidified product (sulfur) of the electronic insulating material.

[0165] Similarly, by further configuring a separator 38 between the semi-solid negative electrode active material layer 33 and the solid electrolyte membrane 32, it is possible to prevent the negative electrode active material, the conductive aid, the hot melt solidified product (sulfur) of the electronic insulating material, etc. from coexisting in the presence of the electrolyte, and it is possible to prevent the side reaction of the negative electrode active material or the conductive aid with the hot melt solidified product (sulfur) of the electronic insulating material.

[0166] Preferred embodiments of the Li-ion secondary battery of the present invention are described with reference to the accompanying drawings, but the present invention is not limited to these embodiments except those specified in the present invention. For example, the Li-ion secondary battery of the present invention may have a plurality of solid electrolyte membranes of the present invention. For example, the solid electrolyte membrane of the present invention may be stacked into two layers and used as a separator.

[0167] <Applications of lithium-ion secondary batteries>

[0168] The lithium ion secondary battery of the present invention can be applied to various purposes. The applicable mode is not particularly limited. For example, when it is carried on an electronic device, a notebook computer, a pen input computer, a mobile computer, an e-book reader, a mobile phone, a wireless telephone sub-machine, a pager, a handheld terminal, a portable fax machine, a portable copier, a portable printer, a stereo headset, a camcorder, a liquid crystal television, a portable vacuum cleaner, a portable CD, a small disk, an electric shaver, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, etc. can be listed. As other civilian products, automobiles, electric vehicles, motors, lighting fixtures, toys, game consoles, load regulators, clocks, flashlights, cameras, and medical equipment (pacemakers, hearing aids, and shoulder massagers, etc.) can be listed. Moreover, it can be used as various military products and aviation products. Moreover, it can also be combined with solar cells.

[0169] Among them, it is preferably used in applications that require high capacity and high rate discharge characteristics. For example, in the case of power storage devices that are expected to have large capacity in the future, high safety becomes essential, and compatibility of battery performance is also required. In addition, it can be assumed that a high-capacity secondary battery is installed in an electric car and charged every day at home. According to the present invention, it is possible to well respond to such a usage mode and exert its excellent effect.

[0170] Example

[0171] The present invention will be described in further detail based on examples, but the present invention is not limited to these embodiments.

[0172] [Example 1]

[0173] <Example 1-1> Preparation of solid electrolyte membrane (separator)

[0174] As an oxide-based inorganic solid electrolyte, LLZ (Li7La3Zr2O 12 , particle size 3.0μm, manufactured by Toshima Manufacturing Co., Ltd.) 50 volume%, Al2O3 (particle size 50nm, manufactured by SkySpring Nanomaterials) 25 volume%, sulfur (S, manufactured by Aldrich, purity > 99.98%) 25 volume% were mixed and kneaded at 140°C. Using a roller press heated to 150°C, the mixture was rolled and stretched at 160MPa while sandwiching two pieces of aluminum foil to produce a sheet with a thickness of 3.5μm from the part where the aluminum foil was removed. The sheet was hot-pressed in warm water at 160°C and 550MPa, and then cooled to obtain the solid electrolyte membrane of Example 1-1. The thickness of the obtained solid electrolyte membrane is 3.0μm.

[0175] <Example 1-2> Preparation of Li-ion secondary battery

[0176] <Production of positive electrode sheet>

[0177] 180 zirconia beads with a diameter of 5 mm were placed in a 45 mL zirconia container (manufactured by Fritsch Co., Ltd.), and 2.0 g of LPS (sulfide-based inorganic solid electrolyte) synthesized by the method described in [Reference Example 1] of International Publication No. 2018 / 164051, 0.1 g of styrene butadiene rubber (product code 182907, manufactured by Aldrich, CO. LTD.) and 22 g of octane as a dispersion medium were added. Then, the container was set in a planetary ball mill P-7 manufactured by Fritsch Co., Ltd. and stirred at a speed of 300 rpm for 2 hours at a temperature of 25 ° C. Then, the positive electrode active material LiNi 0.85 Co 0.10 Al 0.05 7.9 g of O2 (lithium nickel cobalt aluminum oxide) was placed in the container, and the container was again placed in the planetary ball mill P-7, and mixing was continued for 15 minutes at a temperature of 25° C. and a rotation speed of 100 rpm. In this way, a positive electrode composition was obtained.

[0178] Next, the obtained positive electrode composition was applied to an aluminum foil with a thickness of 20 μm as a current collector using a baking applicator, heated at 80°C for 2 hours, and dried. Then, the dried positive electrode layer composition was heated (120°C) and pressed (600 MPa, 1 minute) using a hot press to achieve a predetermined density. In this way, a positive electrode sheet having a positive electrode active material layer with a film thickness of 110 μm was prepared.

[0179] On the surface of the solid electrolyte membrane of Example 1-1, the above-mentioned positive electrode sheet is stacked to contact the positive electrode active material layer. In addition, a lithium foil is stacked on the side of the solid electrolyte membrane opposite to the positive electrode sheet side. On the laminate thus obtained, a constraint plate and a screw as a constraint member are used, and the tightening force of the screw is adjusted with a torque wrench, and the constraint pressure is set to 8MPa, thereby obtaining an all-solid-state Li-ion secondary battery of Example 1-2.

[0180] [Example 2]

[0181] <Example 2-1> Preparation of solid electrolyte membrane (separator)

[0182] In Example 1-1, a solid electrolyte membrane (thickness 8.5 μm) of Example 2-1 was obtained in the same manner as in Example 1-1 except that the particle size of LLZ used was changed to 8.0 μm.

[0183] <Example 2-2> Preparation of Li-ion secondary battery

[0184] Using the solid electrolyte of Example 2-1, an all-solid-state Li ion secondary battery of Example 2-2 was obtained in the same manner as in Example 1-2.

[0185] [Comparative Example 1]

[0186] <Comparative Example 1-1> Preparation of solid electrolyte membrane (separator)

[0187] As an oxide-based inorganic solid electrolyte, LLZ (Li7La3Zr2O 12 , particle size 3.0μm, manufactured by Toshima Manufacturing Co., Ltd.) 50 volume%, Al2O3 (particle size 500nm, manufactured by SkySpring Materials) 25 volume%, sulfur (S, manufactured by Aldrich, purity> 99.98%) 25 volume% were mixed and kneaded at 140°C. Using a roller press heated to 150°C, the kneaded product was rolled and stretched at 24MPa with two pieces of aluminum foil sandwiched between them to produce a sheet with a thickness of 100μm from the portion where the aluminum foil was removed. The obtained sheet was cooled, the aluminum foil was peeled off, and the solid electrolyte membrane of Comparative Example 1-1 was obtained.

[0188] <Comparative Example 1-2> Preparation of Li-ion Secondary Battery

[0189] Using the solid electrolyte membrane of Comparative Example 1-1, an all-solid-state Li ion secondary battery of Comparative Example 1-2 was obtained in the same manner as in Example 1-2.

[0190] [Comparative Example 2]

[0191] <Comparative Example 2-1> Preparation of solid electrolyte membrane (separator)

[0192] A solid electrolyte membrane (thickness 100 μm) of Comparative Example 2-1 was obtained in the same manner as in Comparative Example 1-1, except that Al 2 O 3 having a particle size of 50 nm (the same as in Example 1-1) was used.

[0193] <Comparative Example 2-2> Preparation of Li-ion Secondary Battery

[0194] Using the solid electrolyte membrane of Comparative Example 2-1, an all-solid-state Li ion secondary battery of Comparative Example 1-2 was obtained in the same manner as in Example 1-2.

[0195] [Comparative Example 3]

[0196] <Comparative Example 3-1> Preparation of solid electrolyte membrane (separator)

[0197] In Example 1-1, a solid electrolyte membrane (thickness 3.5 μm) of Comparative Example 3-1 was obtained in the same manner as in Example 1-1 except that the stretching by the roll press was set to 150° C. and 24 MPa and hot water hot pressing was not performed.

[0198] <Comparative Example 3-2> Preparation of Li-ion Secondary Battery

[0199] Using the solid electrolyte membrane of Comparative Example 3-1, an all-solid-state Li ion secondary battery of Comparative Example 3-2 was obtained in the same manner as in Example 1-2.

[0200] [Test example]

[0201] <Evaluation of the state of the hot melt solidified product of sulfur>

[0202] By using the above-mentioned micro-Raman spectroscopy, it was investigated whether the hot melt solidified material of sulfur filling between the solid particles was in an amorphous state or a crystallized state.

[0203] <Evaluation of charge-discharge cycle characteristics>

[0204] Using each of the all-solid-state Li-ion secondary batteries produced above, charge and discharge were performed under the following conditions to conduct a charge and discharge cycle characteristic test: one charge followed by one discharge was defined as one cycle.

[0205] (condition)

[0206] At 30°C and a current density of 0.09 mA / cm 2 (equivalent to 0.05C), 4.2V, constant current condition (0.36mA / cm 2 )

[0207] When an internal short circuit occurs, charging is not complete, so charging is stopped within 50 hours and the battery is discharged. The presence of an internal short circuit is determined by whether there is a sharp voltage drop during charging.

[0208] The charge and discharge cycle characteristics were evaluated according to the following evaluation criteria.

[0209] -Charge and Discharge Cycle Characteristics Evaluation Criteria-

[0210] A: No short circuit for more than 3 cycles

[0211] B: Short circuit when more than 2 cycles and less than 3 cycles

[0212] C: Short circuit when more than 1 cycle and less than 2 cycles

[0213] D: Short circuit when less than 1 cycle

[0214] The results are shown in the following table.

[0215] [Table 1]

[0216]

[0217] As shown in the above table, the solid electrolyte membrane of the present invention has an extremely thin film shape in which inorganic solid electrolyte particles are arranged in a substantially single layer to suppress battery resistance, but a Li ion secondary battery using the membrane as a separator has excellent charge and discharge cycle characteristics.

[0218] The solid electrolyte membrane of the present invention uses a membrane with electrolyte resistance as an inorganic solid electrolyte. Therefore, it can be seen that the solid electrolyte membrane of the present invention can be used as a separator in any form of Li ion secondary battery, such as an electrolyte secondary battery and an all-solid secondary battery, and can suppress the battery resistance of the obtained Li ion secondary battery while further improving the cycle characteristics of the Li ion secondary battery.

[0219] The present invention has been described together with its embodiments, but unless otherwise specified, the present invention is not limited in any detail in the description and should be interpreted broadly without departing from the gist and scope of the invention set forth in the claims.

[0220] This application claims priority based on Japanese Patent Application No. 2019-197748 filed in Japan on October 30, 2019, which are hereby incorporated by reference, and the contents thereof are incorporated into this specification as a part of what is described in this specification.

[0221] Explanation of symbols

[0222] 10-all-solid-state secondary battery, 1-negative electrode collector, 2-negative electrode active material layer, 3-solid electrolyte layer, 4-positive electrode active material layer, 5-positive electrode collector, 6-working part, 21, 31-semi-solid positive electrode active material layer, 22, 32, 42-solid electrolyte membrane (separator), 23-solid electrolyte layer (layer containing sulfide-based inorganic solid electrolyte), 24-metal lithium layer (Li foil), 25, 34, 44-inorganic solid electrolyte particles, 26, 35, 45-electronic insulating inorganic particles, 27, 36, 46-hot-melt solidified product of electronic insulating material, 28, 37, 38-separator, 33-semi-solid negative electrode active material layer, 41-all-solid positive electrode active material layer, 43-all-solid negative electrode active material layer.

Claims

1. A semi-solid lithium ion secondary battery comprising a solid electrolyte membrane, a positive electrode layer and a negative electrode layer, The solid electrolyte membrane has: Electronically insulating inorganic particles with a particle size of 10 to 500 nm, Inorganic solid electrolyte particles having a particle size larger than the electronically insulating inorganic particles and having electrolyte resistance and ion conductivity, and a hot melt solidified product of an electronic insulating material that fills the gaps between the particles and is solid at 100° C. and heat-melts in a temperature range of 200° C. or less; The positive electrode layer is arranged on one side of the solid electrolyte membrane; The negative electrode layer is arranged on a side of the solid electrolyte membrane opposite to a side on which the positive electrode layer is arranged. At least one of the positive electrode layer and the negative electrode layer includes a semi-solid active material layer containing an electrolyte solution, The hot melt solidified product of the electronic insulating material is in a non-crystalline state, The thickness of the solid electrolyte membrane is greater than or equal to [the particle size of the inorganic solid electrolyte particles×0.7] and less than or equal to [the particle size of the inorganic solid electrolyte particles×1.3], The particle size of the electronically insulating inorganic particles and the particle size of the inorganic solid electrolyte particles are the volume-based median diameter, i.e., d50. The thickness of the solid electrolyte membrane is the value obtained by measuring the thickness at 50 locations at intervals of 10 μm relative to the cross-section of the solid electrolyte membrane and averaging them.

2. The semi-solid lithium ion secondary battery according to claim 1, wherein: The positive electrode active material layer constituting the positive electrode layer is a semi-solid positive electrode active material layer containing an electrolyte solution. The thickness of the semi-solid positive electrode active material layer is 200 to 2000 μm.

3. The semi-solid lithium ion secondary battery according to claim 1 or 2, wherein: The negative electrode active material constituting the negative electrode layer includes metallic lithium.

4. The semi-solid lithium ion secondary battery according to claim 1 or 2, wherein: The negative electrode active material layer constituting the negative electrode layer is a semi-solid negative electrode active material layer containing an electrolyte solution.

5. The semi-solid lithium ion secondary battery according to claim 1 or 2, wherein: The positive electrode active material layer constituting the positive electrode layer is a semi-solid positive electrode active material layer containing an electrolyte, and the negative electrode active material layer constituting the negative electrode layer is a semi-solid negative electrode active material layer containing an electrolyte. The electrolyte of the semi-solid negative electrode active material layer and the electrolyte of the semi-solid positive electrode active material layer are different electrolytes.

6. The semi-solid lithium ion secondary battery according to claim 1 or 2, wherein: The electronically insulating inorganic particles and the inorganic solid electrolyte particles have the same composition.

7. The semi-solid lithium ion secondary battery according to claim 1 or 2, wherein: The particle size of the electronically insulating inorganic particles and the particle size of the inorganic solid electrolyte particles satisfy the following formula: 5≤[particle size of inorganic solid electrolyte particles] / [particle size of electronically insulating inorganic particles].

8. The semi-solid lithium ion secondary battery according to claim 1 or 2, wherein: The content of the inorganic solid electrolyte particles in the solid electrolyte membrane is 10 to 90 volume %, and the content of the electronically insulating inorganic particles is 5 to 45 volume %. The particle size of the inorganic solid electrolyte particles is 1 to 20 μm.

9. The semi-solid lithium ion secondary battery according to claim 1 or 2, wherein: The content of the inorganic solid electrolyte particles in the solid electrolyte membrane is 40 to 60% by volume, and the content of the thermally molten solidified product of the electronic insulating material is 10 to 40% by volume.

10. The semi-solid lithium ion secondary battery according to claim 1 or 2, wherein: The positive electrode active material layer constituting the positive electrode layer is a semi-solid positive electrode active material layer containing an electrolyte solution. A separator is further arranged between the semi-solid cathode active material layer and the solid electrolyte membrane.

11. The semi-solid lithium ion secondary battery according to claim 10, wherein: The negative electrode active material layer constituting the negative electrode layer is a semi-solid negative electrode active material layer containing an electrolyte. A separator is further arranged between the semi-solid negative electrode active material layer and the solid electrolyte membrane.